Hubungan Konformitas Dengan Perilaku Konsumtif Pada Penggemar Stray Kids - Sarazwati, Ella Fransiska; Putri, Ellyana Ilsan Eka (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
The formation of fan groups as a result of the significant influence of K-Pop culture in Indonesia often leads to the phenomenon of conformity. One consequence of this conformity phenomenon among fans is consumptive behavior. The aim of this study is to determine the relationship between conformity and consumptive behavior among Stray Kids fans. The method used in this study is quantitative research with a sample size of 100 subjects aged 17-24 years, who are fans of Stray Kids, and have purchased Stray Kids merchandise. The sampling technique used is purposive sampling. Data analysis was conducted using the Pearson Product Moment correlation method, resulting in a correlation coefficient of 0.596 (r=0.596) with a significance value of 0.00 (p<0.05). Therefore, these results indicate that there is a relationship between conformity and consumerist behavior among Stray Kids fans.